Enterobius vermicularis in Immunocompromised Patients: A Case Report - Sangitha Jayagandan; Oudhaya Kumaran; Nonika Rajkumari (Journal of Clinical and Diagnostic Research)
One of the most prevalent nematode infections globally is Enterobius vermicularis, commonly known as pinworm. This infection is often seen among children living in poor socioeconomic conditions, in overcrowded households, and in immunocompromised patients with uncontrolled diabetes, hypertension, long-term steroid therapy, and other related issues. With treatment, the cure rate is between 90 to 95%. However, reinfection is frequent, particularly in cases where contacts are not treated concurrently. Hereby, the authors present a case report of two male patients (58 and 40 year-old) with uncontrolled diabetes mellitus who presented with pinworm infections in unconventional sites. Enterobius vermicularis can manifest in uncommon locations such as the caecum, the appendix, and other visceral organs of the abdomen, including the uterine endometrium. These atypical presentations can lead to more serious complications, such as granuloma and abscess formation, which may even result in infertility. Although pinworm infection is typically considered a childhood disease, immunosuppressed adults are also susceptible.